Renewable fuels from biomass-derived compounds: Ru-containing hydrotalcites as catalysts for conversion of HMF to 2,5-dimethylfuran - Nagpure, Atul S.; Venugopal, Ashok Kumar; Lucas, Nishita; Manikandan, Marimuthu; Thirumalaiswamy, Raja; Chilukuri, Satyanarayana V. (Catalysis Science & Technology, 2015)
Production of transportation fuels from renewable biomass is hugely important considering the current ecological concerns over CO2 built up in the atmosphere. Ruthenium-containing hydrotalcite (HT) catalysts were applied for the selective hydrogenolysis of biomass-derived 5-hydroxymethylfurfural (HMF) to 2,5-dimethylfuran (DMF). Structural and morphological features of the catalysts were examined using various physico-chemical characterization techniques. The influence of various reaction parameters, such as reaction temperature, solvent, Ru content of the catalyst, etc., was investigated with respect to HMF conversion and DMF yield. The study clearly shows that well-dispersed Ru nanoparticles are highly active and selective in the conversion of HMF to DMF. A catalyst containing only 0.56 wt% Ru converted 100 mol% HMF to yield 58 mol% DMF. This catalyst was found to be recyclable as the activity was retained even after five cycles of reaction. 2-Propanol was found to be a good solvent as it helped to improve DMF yield through transfer hydrogenation. Based on the results of the investigations, a reaction pathway for the conversion of HMF to DMF was proposed for the present Ru-based catalyst system.

Role of surface synergistic effect on the performance of Ni-based hydrotalcite catalyst for highly efficient hydrogenation of furfural - Manikandan, Marimuthu; Venugopal, Ashok Kumar; Prabu, Kandasamy; Jha, Ratnesh Kumar; Thirumalaiswamy, Raja (Journal of Molecular Catalysis A-Chemical, 2016)
The selective vapor phase hydrogenation of furfural at ambient pressure has been investigated using a facile and robust hydrotalcite derived Ni containing mixed oxide catalyst. The systematic characterization results conferred that the difficulty in the reduction of Ni species due to the strong interaction between Ni and support, which facilitated from the homogeneous distribution of hydrotalcite structure. It was also found that the structure and catalytic performance of the catalysts were greatly influenced by Ni loading. Through fine-tuned surface elemental sites and reaction conditions, furfural conversion of 98% with 95% of furfuryl alcohol selectivity was achieved over a MAN-2 catalyst containing two molar ratio of Ni. The results have demonstrated that the incorporation of Mg significantly enhances the Ni-support interaction, Ni dispersion and catalytic performance. The high efficiency of the Ni-based hydrotalcite derived catalyst was mainly attributed to the surface synergistic interaction between the catalytically active metallic Ni sites and the strong basic sites, which furnished an eco-benign and sustainable catalyst for the selective hydrogenation of furfural. Furthermore, the spent catalyst analysis substantiated that no significant difference in the catalyst phase was observed even after 48 h of reaction stream. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: alcohol-hydrotalcites-selective; Biomass-frurfural-furfuryl; Hydrogenation